Clinical predictors of readmission after surgery for Hirschsprung disease. Issue 11 (19th March 2021) - Min, Jie; Cai, Peng; Wu, Bin; Gu, Zhicheng; Huang, Shungen; Wang, Jian
Abstract : Abstract: The reasons for readmission of children with Hirschsprung disease (HD) are multiple. The study aims to predict the relevant factors for the readmission of children with HD by collecting and analyzing the relevant data of the child's admission to the hospital at the time of surgery. A retrospective review was performed including all patients with surgical treatment of HD at our institution between the years of 2011 to 2020. Univariate and multivariate Logistic regression analysis were performed to obtain the independent risk factor for this study. The receiver operating characteristic curve (ROC) were used to assess the performance of derived models. A total of 162 patients were identified. The average presurgery weights were 6.93 ± 1.78 kg in the readmission group and 8.38 ± 3.17 kg in the non-readmission group. Six children were classified as a low-weight in the readmission group, and 11 children classified as low-weight in the non-readmission group. The length of the intestinal tube after resection was 25.25 ± 15.21 cm in the readmission group, and 16.23 ± 4.10 cm in the non-readmission group. The ROC for the prediction model of readmission after HD surgery (AUC = 0.811). In children undergoing the HD surgery, we showed preoperative low body weight and long intra-operative bowel resection significantly increase the probability of readmission due to complications.